Field assessment of thermal comfort performance in lecturers' room / Nurain Syamimi Aju and Norishahaini Mohamed Ishak - Aju, Nurain Syamimi; Mohamed Ishak, Norishahaini (2018)
A comfort level of a person is a subjective substance and has been one of the most important elements in achieving maximum productivity. To obtain the current state of comfort among lecturers in one of higher learning institutions in Malaysia, a questionnaire survey and measurements were conducted in the lecturers' room in the Faculty of Architecture, Planning and Surveying (FSPU) in Universiti Teknologi MARA Perak. The questions were designed based on ASHRAE 7-point scale and previous literature reviews. Measurements were conducted in 33 lecturers' room by using Delta Ohm and Grey Globe, along with the distribution of the questionnaire. The main objective of this study is to determine the level of comfort from the lecturers' point of view during their hours in the office by comparing the Predicted Mean Vote (PMV), Percentage of Predicted Dissatisfied (PPD) counted as the objective measurement, and TSV (Thermal Sensation Vote) which is the subjective measurement. Since the office rooms are situated in a mechanically conditioned building, the supposedly comfort temperature is 24°C.